2017
DOI: 10.1111/resp.13232
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with community‐onset pneumonia at low risk of drug‐resistant pathogens: Impact of β‐lactam plus macrolide combination therapy

Abstract: In patients with community-onset pneumonia at low DRP risk, BLM treatment reduced 30-day mortality compared with BL. Independent risk factors for mortality are potential confounding factors when assessing antibiotic effects in randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…There are limited published data evaluating the effects of antibiotic in CAP according to the DRP risk. In a post hoc analysis of a prospective multicentre cohort of patients with CAP, Okumura et al have shown that β‐lactam and macrolide in combination reduced the 30‐day mortality (adjusted odds ratio: 0.28, 95% CI: 0.09–0.87) compared with β‐lactam alone. In addition, among patients at low risk for CAP‐DRP, independent host factors associated with mortality included high arterial carbon dioxide (PaCO 2 ) level, non‐ambulatory status, leucopenia, low haematocrit, older age, tachypnoea, low serum albumin level and low body temperature.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…There are limited published data evaluating the effects of antibiotic in CAP according to the DRP risk. In a post hoc analysis of a prospective multicentre cohort of patients with CAP, Okumura et al have shown that β‐lactam and macrolide in combination reduced the 30‐day mortality (adjusted odds ratio: 0.28, 95% CI: 0.09–0.87) compared with β‐lactam alone. In addition, among patients at low risk for CAP‐DRP, independent host factors associated with mortality included high arterial carbon dioxide (PaCO 2 ) level, non‐ambulatory status, leucopenia, low haematocrit, older age, tachypnoea, low serum albumin level and low body temperature.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…In this issue of Respirology , Okumura et al . add to the already extensive body of literature suggesting that optimal empiric therapy for CAP is a macrolide and a beta‐lactam.…”
mentioning
confidence: 99%
“…In summary, those that continue to believe that the data are flawed and do not wish to give a macrolide are unlikely to be swayed by the study by Okumura et al . While it is possible that tetracyclines have similar anti‐inflammatory and anti‐toxin functions to macrolides, the lack of any significant studies to show a comparative clinical benefit signifies that they cannot be recommended as empiric therapy in the place of a macrolide.…”
mentioning
confidence: 99%
See 2 more Smart Citations